Legal conditions of EU energy security - Jānis Teivāns-Treinovskis; Nikolajs Jefimovs; Ruta Velika; Igors Trofimovs (Entrepreneurship and Sustainability Issues, 2023)
Despite the high level of technological and civilisational development of Western society, its prosperity and sustainability of development most directly depend on energy policy. Quite often, the field of energy security determines which countries are leading and decisive in the world economy and global competitiveness. The latest geopolitical events, namely the Russian military aggression on Ukraine's territory, showed that most European countries, including Russia itself, increasingly depend on individual energy resources. Such a situation creates serious challenges that must be promptly and effectively responded to. One of the most severe challenges is energy blackmail, which is purposefully implemented by the leadership of the Russian Federation to achieve its goals in Ukraine. The threat of destroying Ukraine's energy system is no less severe, and a humanitarian disaster may also follow in this European and Western-oriented country. Unable to defeat Ukraine on the battlefield, the Russian Federation is trying to force the Ukrainian leadership to agree to an actual capitulation by methodically destroying its energy sector. This shows that the European Union must be able to respond to the problems of its energy sector and provide support to its allies to guarantee energy security. In addition, this type of response must comply with international and national law.